Meningkatkan Keaktifan dan Hasil Belajar Melalui Model PBL Pada Siswa Kelas I SD Kanisius Kintelan I - Munawaroh, Isti; Amelia, Maria Agustina; Sarwi, Marciana (Paedagogie, 2024)
Through the application of the Problem Based Learning (PBL) learning model framework in the subject of Pancasila education in the independent curriculum, this research seeks to increase learning activity and learning outcomes for class I SD Kanisius Kintelan 1. The research method used in this study was Classroom Action Research (PTK). ) which was carried out in two cycles. There are four stages that are carried out systematically in each research cycle, namely Planning (Planning), Implementation (Acting), Observation (Observing), Reflection (Reflecting). Collecting data in this study using test techniques, questionnaires and observation. The research subjects were class I SD Kanisius Kintelan 1, totaling 13 students consisting of 5 male students and 8 female students. The results of observations show the problem of student activity and student disinterest in lecture learning. Actions taken by implementing the problem based learning model of learning. The results of the study show that the application of the problem-based learning model can improve learning activity and learning outcomes for first grade students at Kanisius Kintelan 1 Elementary School, Yogyakarta.